Key Deposition Parameters for Short-type ZnO Nanosheets Electrodeposited Under Galvanostatic Mode - Ensang Timuda, Gerald; Harjanto, Dhimas; Widayatno, Wahyu Bambang (Makara Journal of Science, 2020)
Studies on the deposition of ZnO nanosheets grown vertically and perpendicular to conductive substrates have been conducted to obtain tall-type nanosheets (approximately 15 µm in height). However, some applications require short-type nanosheets with a height of about 1µm or less. In this study, short-type ZnO nanosheets were electrodeposited on indium-doped tin oxide substrates under galvanostatic (constant current) mode for a short deposition time. Then, the key parameters to form nanosheet layers with a height in the micrometer order and with good coverage were evaluated. Deposition was performed at 1 mA/cm2 for 60 s. Ar gas was initially bubbled into the electrolyte solution during electrodeposition to remove oxygen. Then, the solution was compared with solutions that did not undergo bubbling. Various electrolyte compositions (various concentrations of acetate and nitrate) were observed in solutions under the non-Ar bubbling condition. Moreover, the oxygen in the solution remarkably affected the morphology of the nanosheet, which became much denser and taller. Therefore, altering electrolyte composition affects morphology, although the effect is not as significant. Electrolyte composition must be optimized to produce the desired short and dense nanosheets because a low concentration of each anion leads to the production of a non-nanosheet layer, whereas a high concentration causes reduction in the density coverage of the nanosheet. A complete discussion of this phenomenon is presented in this study.